Test the Physical Properties of Eye Shadow Preparations with Natural Coloring of Temulawak (Curcuma Xanthorrizzha Roxb) - Shinta Fadhila; Joko Santoso; Wilda Amananti (Jurnal EduHealth, 2025)
Introduction: Temulawak contains curcuminoid compounds. Apart from curcuminoids, Temulawak also contains volatile substances suc as isofuranogermakren, tricycline, alloaromadendren, germakren, and zanthorriza. Active components that are very effective as antioxidants in ginger rhizomes include curcumin, demotoksicurmin, and bisdemotoksicurcumin. Curcumin is a natural chemical compound that can be used for natural coloring. Objective: This research aims to find out whether ginger extract can be a safe and good natural coloring ingredient in eye shadow preparations that is in accordance with the physical properties test. Method: This research applies a total sampling method. The method used is the ginger juice extract method which is obtained directly or can be called an experiment. Conclusion: Curcuma extract can be used as a safe and effective natural coloring for eye shadow preparations, according to the results of physical properties tests which include organoleptic tests, pH tests, homogeneity tests,irritation tests, and liking tests.